Pengaruh Risiko Kredit Dan Efisiensi Operasional Terhadap Kinerja Keuangan Pada Perusahaan Perbankan Konvensional Yang Terdaftar di Bursa Efek Indonesia - Nur Azizah Syamsuddin; Rifqi Nur Wahyudi (Program Studi Administrasi Fiskal, 2025)
ABSTRACT This study aims to analyze the influence of credit risk and operational efficiency on the financial performance of conventional banking companies listed on the Indonesia Stock Exchange during the period 2021–2024. The approach used in this study is quantitative with the type of causal research. The data used is secondary data in the form of annual financial statements. Credit risk is measured using Non-Performing Loans (NPLs), operational efficiency is measured by the ratio of Operating Costs to Operating Income (BOPO), and financial performance is measured through Return on Assets (ROA). The results of the analysis show that partially credit risk (NPL) and operational efficiency (BOPO) have a negative and significant effect on financial performance (ROA). However, credit risk does not have a significant effect on operational efficiency. Simultaneously, credit risk and operational efficiency have a significant effect on financial performance, with a determination coefficient value (R²) of 69.1%, indicating that independent variables make a significant contribution to dependent variables. These findings indicate the importance of credit risk management and cost efficiency improvements in order to increase the profitability and stability of banking institutions. This research makes a theoretical and practical contribution to the development of risk management strategies and operational efficiency in an effort to improve the financial performance of banking companies in Indonesia, especially after the COVID-19 pandemic.